In-hospital cardiac arrest in hospitals with mature rapid response systems — a multicentre, retrospective cohort study. (April 2020) - Tirkkonen, Joonas; Skrifvars, Markus B.; Parr, Michael; Tamminen, Tero; Aneman, Anders
Abstract: Aim: To investigate in-hospital cardiac arrests (IHCAs) according to the Ustein template in hospitals with mature systems utilizing rapid response teams (RRTs), with a special reference to preceding RRT factors and factors associated with a favourable neurological outcome (cerebral performance category (CPC) 1–2) at hospital discharge. Methods: Multicentre, retrospective cohort study between 2017–2018 including two Finnish and one Australian university affiliated tertiary hospitals. Results: A total 309 IHCAs occurred with an incidence of 0.78 arrests per 1000 hospital admissions. The median age of the patients was 72 years, 63% were male and 73% had previously lived a fully independent life with a median Charlson comorbidity index of two. Before the IHCA, 16% of the patients had been reviewed by RRTs and 26% of the patients fulfilled RRT activation criteria in the preceding 8 h of the IHCA. Return of spontaneous circulation was achieved in 53% of the patients and 28% were discharged from hospital with CPC 1–2. In a multivariable model, younger age, no pre-arrest RRT criteria, arrest in normal work hours, witnessed arrest and shockable initial rhythm were independently associated with CPC 1–2 at hospital discharge. Conclusions: In hospitals with mature rapid response systems most IHCA patients live a fully independent life with low burden of comorbid diseases before their hospital admission, the IHCA incidence is low and outcome better than traditionally believed. Deterioration before IHCA is present in a significant number of patients and improved monitoring and earlier interventions may further improve outcomes.